2009
DOI: 10.1007/s12253-009-9177-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Non-Sentinel Lymph Node Status After Positive Sentinel Biopsy in Breast Cancer: What Model Performs the Best in a Czech Population?

Abstract: Several models have previously been proposed to predict the probability of non-sentinel lymph node (NSLN) metastases after a positive sentinel lymph node (SLN) biopsy in breast cancer. The aim of this study was to assess the accuracy of two previously published nomograms (MSKCC, Stanford) and to develop an alternative model with the best predictive accuracy in a Czech population. In the basic population of 330 SLN-positive patients from the Czech Republic, the accuracy of the MSKCC and the Stanford nomograms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 28 publications
1
45
0
1
Order By: Relevance
“…However, the variables with no proven statistical significance contribute to the predictive power of the model. The same conclusion has been drawn when constructing MSKCC [17] and MOU [19] models.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the variables with no proven statistical significance contribute to the predictive power of the model. The same conclusion has been drawn when constructing MSKCC [17] and MOU [19] models.…”
Section: Discussionsupporting
confidence: 71%
“…However, other papers suggest the risk estimation given by the model helps (better than expert opinion) to decide the relevance of completion of axillary dissection [18]. The characteristics of this and other models are summarized in table 1 [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid performing ALND for non-SLN-negative patients with SLN-positive axilla, nomograms and scoring systems for predicting the status of the axillary non-SLNs have been developed in many centers (Van Zee et al, 2003;Degnim et al, 2005;Smidt et al, 2005;Chapgar et al, 2006;Pal et al, 2008;Alran et al, 2007;Kohrt et al, 2008;Cho et al, 2008;Coufal et al, 2009;Gur et al, 2010;Perhavec et al, 2010;Lombardi, et al, 2011;Mittendorf et al, 2012;Meretoja et al, 2012;Derici et al, 2012). Many studies have tested these models and have obtained varying results (Van Zee et al, 2003;Kocsis et al, 2004;Degnim et al, 2005;Soni et al, 3 2005; Lambert et al, 2006;Ponzone et al, 2007;Pal et al, 2008;Kohrt et al, 2008;Cho et al, 2008;Klar et al, 2008;Poirier et al, 2008;Coufal et al, 2009;Coutant et el., 2009;Scow et al, 2009;Gur et al, 2010;Moghaddam et al, 2010;Hessman et al, 2011;Hidar et al, 2011;Lombardi et al, 2011;Tan et al, 2011;Derici et al, 2012;Chen et al, 2012;Zhu et al, 2012;Sasada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bols ter et al and Co u fal et al sta ted that the in ciden ce of n-SLN me tas ta ses was re la ted to the si ze of the SLN me tas ta ses. 18,19 The re sults of a number of stu di es in the li te ra tu re indicate a di rect relationship bet we en SLN me tas ta sis and age, pri mary tumor di a me ter, lympha tic in va si on and ve no us/vascu lar in va si on. 20,21 Tur ner et al sta ted that pri mary tu mor di a me ter indicated a high risk for SLN me tasta sis.…”
Section: Discussionmentioning
confidence: 99%